Social gains or losses? Evidence from dairy systems under alternative herd health management practices in Kenya - Kevin W. Maina; Martin Christoph Parlasca; Elizaphan James Oburu Rao (University of Bonn, Center for Development Research (ZEF), 2024)
Strategies for sustainable intensification of livestock are becoming increasingly important in designing interventions to develop the sector. In dairying systems, herd health management is among such strategies. While adoption patterns and productivity gains have been analyzed in previous studies, the social implications are still not well understood. This paper provides insights into the relationship between herd health management and intra-household labor demand as well as women empowerment. We test the hypotheses that the adoption of herd health management practices (HHPs) increases intra-household labor demand among male and female household members and, thereby, affects women empowerment. We use primary data from smallholder dairy farmers in Kenya on time use, women's participation in decision-making and livestock asset ownership, adoption status of important HHPs, as well as household demographic characteristics and apply censored regression and multinomial logit regression models to test our hypotheses. The results show that adopting HHPs is associated with more labor demand in dairy production for both men and women. The magnitude of the change differs across production systems but is always higher for men. Additionally, herd health management practices are negatively associated with different aspects of women empowerment including women's livestock asset ownership and control over income from dairy. The study underscores the importance for gender-sensitivity in the sustainable intensification of livestock production in the Global South.
Keywords: C31; D13; O12; O33; Q16; Q18; 330; Herd health management; gender; labor demand; dairying; Greenhouse gases (GHGs)